8. Influences of Physical and Imagined Others in Music Students’ Experiences of Practice and Performance - Andrea Schiavio; Henrique Meissner; Renee Timmers (Psychological Perspectives on Musical Experiences and Skills: Research in the Western Balkans and Western Europe, 2024)
Musical tasks are commonly undertaken either individually or within a group setting, often with the additional presence of an audience. While these scenarios entail distinct social contexts, our study delves into crossovers: we explore how the social dimension permeates individual contexts and, conversely, how individual experiences are woven into social settings. To do so, we asked music higher education students based in the Netherlands and the United Kingdom to reflect on their felt experiences of others who may be imagined or physically present during individual and group practice or performance. Qualitative findings highlight the role of perspective-taking and attentional focus, the experienced differences between in-person communication and imagined intersubjectivity, the role of trust and opportunity for creative freedom, and the strongly valenced implications of the perspectives on self and others. These themes are seen as opening avenues for further investigation with relevance to music education to explicitly consider how students experience and think about others.